Entomopathogenic Fungi for the Management of Calopepla leayana on Gmelina arborea - S. Murugesan, N. Senthilkumar* and (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Entomopathogenic fungi, Beauveria bassiana and Metarhizium anisopliae were isolated and identified as natural pathogens of Calopepla leayana. Both the species of fungi were effective against the larval and adult stages of C. leayana causing white and green muscardine diseases respectively. It was also found that B. bassiana was more pathogenic to the pest as compared to M. anisopliae.Â The susceptibility of larvae and adults was negatively associated with the age and positively associated with the fungal spore concentration. In all the stages from I instar to adult, the highest mortality was observed in 10% of 1x109 spores/ml concentration of B. bassiana among 1, 2.5, 5 & 10% of 1x109 spores/ml concentration.Â It was also reflected in probit analysis that the concentration of spores required to kill fifty percent of the population was ranges from 0.09% to 5.98% of 1x109 spores/ml concentration of B. bassiana and 1.02% to 9.72% of 1x109 spores/ml concentration of M. anisopliae. The larvae of I instar have shown highest mortality, which gradually decreased with the increase in age or decrease in the concentration of fungal spores. Mass production of B. bassiana using different substrates was attempted to harvest ample amount of spores. This study revealed that spore production was directly proportional to the mycelial weight and incubation period. From the seven substrates tested, wheat flour was identified as one of the suitable substrates for the mass production of B. bassiana.Â A field trial was conducted to test their efficacy under field conditions. 72-93% mortality was observed in field conditions. <span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">—————————————————————————————————– <span style="font-size: 10pt; line-height: 110%; font-family: Garamond; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> Division of Bioprospecting, Institute of Forest Genetics and Tree Breeding, Coimbatore-641002, Tamilnadu, India *Corresponding author, Email: senthilnj@hotmail.com Cite This Article As: N. Senthilkumar and S. Murugesan. 2010. Entomopathogenic Fungi for the Management of Calopepla leayana on Gmelina arborea. J. Ecobiotechnol. 2(3): 01-06